The Implementation Of Marketing Management Strategies At Roti Rocis Company In South Tangerang - Dwiky Fitriansyah Pahlawan; Sirta Nur Syam Wokas; Dhobith Khoirul Umam; Dendy Angga Pradipta; Agus Hidayat; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2022)
The purpose of this study was to describe the implementation of marketing management strategies at the Roti Rocis Company in Graha Bintaro, South Tangerang. This research uses a qualitative method approach, namely a case study that produces descriptive data that is stated in words. Data collection techniques were carried out by using observation, interviews and literature studies. The data analyzed is from the results of interviews with the owner of the Rocis Bread Company. The results showed that the strategy in increasing the turnover of bread sales at the company, namely the segmentation, targeting, positioning and especially marketing mix strategies had been implemented well, although not fully implemented. To be able to achieve an increase in sales turnover at the company in the bakery food business, the company should be able to innovate the products sold by the company, expand the sales market, add promotional activities and expand bread storage in order to produce more bread.